Intelligence Strategy in Enhancing Loading and Unloading Activities to Achieve Volume Targets: A Case Study of Teluk Lamong - Kurniawan, Stalone Erio; Arthur Josias Simon Runturambi, (Technium Social Sciences Journal, 2024)
Efficient and effective handling of loading and unloading processes at ports is key to achieving set volume targets. In this context, intelligence strategy plays a crucial role in strengthening loading and unloading activities. This study aims to analyze how the implementation of intelligence strategy can enhance loading and unloading activities at Teluk Lamong Port. Through a case study approach, we explore the implementation of intelligence strategy by port authorities and its impact on achieving volume targets. The research findings indicate that well-integrated intelligence strategies can provide timely and relevant information to stakeholders, enabling more efficient resource management and enhancing coordination among various parties involved. The practical implications of these findings underscore the importance of employing intelligence strategies to enhance productivity and operational efficiency at ports, thereby contributing to the attainment of set volume targets.